Expresión escrita: pilotajes, plantillas, atomización, análisis y aprendices de 6 años - Allué Villanueva, Consuelo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2012)
In this article we refer to some pilot work on writing in Primary and Secondary Education in which we have participated. We focus on the effectiveness of the use of templates for the planning of writings; we analyze (with examples) how they help learners to atomize their thought and how they contribute to metalearning. We offer an example of reduction of template to “micro-template”, we analyze two texts by 6-year old learners, and we emphasize the importance of the observation of learners’ work and the influence of their previous models.